DEVELOPMENT OF BIOTECHNOLOGY LEARNING TOOLS BY UTILIZING THE LOCAL POTENTIAL OF CAMPEDAK SKIN TO IMPROVE THE SCIENCE PROCESSING SKILLS OF CLASS XII STUDENTS AT MA SABILARRASYAD SAMARINDA - Patang, Nurfadilah A.; Masswaet, Elsje Theodora; Palenewen, Evie; Hudiyono, Yusak; Tarigan, Daniel; Susilo, susilo (Jurnal Pendidikan Matematika dan IPA, 2024)
ABSTRACTThis research aimed to produce Biotechnology learning tools by utilizing the local potential of cempedak peel to improve the science process skills of class XII students and determine its validity and effectiveness. This is development research that refers to Borg Gall"™s model modified by Sugiono. The trial subjects were students of class XII at Islamic Senior High Boarding School (Madrasah Aliyah) Sabilarrasyad Samarinda. Each of the product, control and field trial subjects consists of 20 students in each class. The research results were in the form of learning tools which include: a syllabus, lesson plan (RPP), student worksheet (LKPD), and assessment instruments. The results of this research showed that the learning tools that have been developed obtained validity with an average percentage of expert assessment of about 96.2% which fulfilled the very valid criteria, and has been proven to be effectively used in learning activities. Based on the T-test results, it can be seen that school learning tools are not similar (there is a significant difference) with the class taught by the researcher using the learning tools that have been developed. Further, it can also be seen from the improvement of students' learning by about 96% and in students' science process skills by 44%.